Mediating effect of emotional response between streamers’ characteristics and consumer purchase intention in E-commerce live streaming - He, Changhua; Hashim, Norliana; Kamarudin, Syafila; Yu, Mengyao; Shi, Lijun (Arts and Science Press, 2024)
Objective: This study aims to explore how streamers' characteristics affect consumers' purchase intentions in e-commerce live streaming. Specifically, the study examines this relationship through the mediating role of emotional responses. Design/Methods: The study sample included 325 e-commerce live streaming consumers from Guangzhou, the most developed city in China for the e-commerce live streaming industry. Random sampling was used in a questionnaire survey to obtain data, while the Statistical Package for the Social Sciences (SPSS) and Analysis of Moment Structures (AMOS) were employed to verify the research hypotheses. Findings: The characteristics of streamers in e-commerce live streaming directly and indirectly impact consumers' purchase intentions. Streamers' characteristics also partially mediate consumers' purchase intentions through emotional responses. Additionally, the results support the mediation model. Practical Significance: The results revealed that the role of streamers is vital in e-commerce live streaming. Furthermore, streamers' professionalism, trustworthiness, and attractiveness significantly affect consumers' purchase intentions. The findings will aid merchants in choosing the right streamers and provide direction for live streaming, improving the professionalism, trustworthiness, and attractiveness of streamers, and increasing sales during live streaming. Originality/Value: The present study contributes to the existing literature by explaining how streamers' characteristics relate to consumers' purchase intentions. The study also examined the mediating processes, thereby promoting an understanding of how consumers' emotional responses influence their purchase intentions.